Potencialni dejavniki tveganja pri delu z izrazno-ustvarjalnimi mediji - Kustec, Klavdija (Socialno delo, 2015)
The use of expressive-creative media in the professions of help and support has been gaining grounds. The aim of the research study is to shed light both on the positive effects of the work with expressive-creative media and their potential negative effects or risk factors, with indicating some of the safety factors of work with expressive-creative media. The results of the qualitative research show that in practice professional workers of related helping professions have not encountered any negative effects in their work with expressive-creative media, while being very much aware of possible risk factors. Accordingly, they developed numerous strategies of alleviating, if not completely avoiding, potential risk factors.
Keywords: kvalitativna raziskava; qualitative research; risks; tveganje; umetnost; art; expert workers; strokovne delavke; safety factors; varovalni dejavniki; umetnostna terapija; art therapy; social work; socialno delo